Kepemimpinan Pendidikan dalam Perspektif Ibnu Jamā’ah Al-Syāfi’ī: Educational Leadership from the Perspective of Ibn Jamā’ah Al-Syāfi’ī - Iskandar Iskandar; Samsuddin Samsuddin; Abdul Jabar Idharudin; Nursalam Siradjuddin (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
Research on educational leadership has largely been dominated by managerial and organizational perspectives, while the contribution of classical Muslim scholars to the development of Islamic educational leadership theory remains underexplored. This study aims to analyze the characteristics of educational leadership in Ibn Jama'ah's thought, reconstruct the educational leadership model embedded in his ideas, and examine its relevance to contemporary educational leadership theory and practice. This study employed a qualitative library research approach. Primary data were obtained from Tadzkirat al-Sāmi‘ wa al-Mutakallim fī Adab al-‘Ālim wa al-Muta‘allim, while secondary data were collected from relevant books and scholarly articles. Data were analyzed using content analysis through data reduction, categorization, interpretation, and conceptual synthesis. The findings reveal that, according to Ibn Jama'ah, teachers function as educational leaders responsible for fostering students' intellectual, moral, spiritual, and social development. The study reconstructs an educational leadership model consisting of three integrated dimensions: leadership based on adab and exemplary conduct, instructional leadership and intellectual development, and educational leadership for character development. This study contributes to the field of educational leadership by extending the concept of instructional leadership through the integration of ethical leadership, moral leadership, and the Islamic concept of murabbi into a holistic value-based model of Islamic educational leadership.